Assessment of the pragmatic component in Down’s syndrome through the Quick Pragmatic Assessment Protocol - Moreno, Esther; Díaz, Félix (Revista de Investigación en Logopedia, 2014)
The literature on the pragmatic component in persons with Down Syndrome (DS) shows no consensus on whether the pragmatic component is a strong asset in these persons or what pragmatic abilities or functions render good performance. The aims of this research have been to (1) analyze the pragmatic features of a person with high-performance DS, and (2) test the usefulness of a specific assessment instrument for this component in this collective. The information was collected by recording language samples in various interaction situations with different conversation partners, in the context of the Association he attends. To analyze the samples we have followed the structure and classification of the Quick Pragmatic Assessment Protocol (Gallardo et al., 2008), which we value for its ease of use, systematicity and clarity. The results of this research provide qualitative information on the pragmatic component in the selected case towards planning general treatment lines. These results constitute a first step towards a more exhaustive study of the pragmatic component in this collective in order to devise more efficient assessment instruments and intervention protocols.
Keywords: Down syndrome; Pragmatics; QPPA.